IMPACT OF STAND STRUCTURE TO THE DIVERSITY OF TREE SAPLING IN RUBBER AGROFOREST SYSTEM - Saida Rasnovi (Jurnal Natural, 2012)
The study of stand structure of rubber agroforest system and its effect on tree sapling diversity was carried out in Bungo District, Jambi Province from August 2004 to August 2005. Basal area (BA) and tree density were surveyed using variable-area transect method. Tree sapling species was surveyed using standard plots combined with circular elementary subplots laid along 60 m transect line. The result shown that BA and tree density of rubber agroforest system were lower significantly with forest at the diameter class 30 cm, but at the diameter class 30 cm there were not differ significantly. PCA analysis shown there was a positive correlation between BA non rubber tree with the species diversity and richness indices of tree sapling in rubber agroforest system and there was no correlation between density of non rubber tree and the indices. However, in the forest, BA and tree density were have a negative correlation with the species diversity and richness indices of tree sapling.